The Power of Resistance Training: Evidence-based Recommendations for Middle-aged and Older Women's Health - Pablo J. Marcos-Pardo; Raquel Vaquero; Gerhard Huber (Retos: Nuevas Tendencias en Educación Física, Deportes y Recreación)
Women have a longer life expectancy, but also a poorer quality of life due to the combined effects of aging and menopause. Among the most widely used non-pharmacological therapies that slow down the effects of these phenomena is resistance training. The aims of this narrative review were: 1) to analyze the strength in health parameters of middle-aged and older women; and 2) to provide a series of practical recommendations for resistance training for women. It was found that resistance training has been shown to prevent and/or treat chronic diseases, improve muscle strength, increase bone density, and reduce the risk of falls and fractures in older women. To conduct our search, we utilized various databases, including MedLine (Pubmed) and Cochrane (Wiley), searching for MeSH-compliant keywords such as: (strength training OR resistance training) AND (middle-aged women OR older women). Our search was limited to manuscripts published from April 1, 2013, to April 1, 2023, although some earlier studies were referenced to provide additional context in certain areas of the narrative review. The narrative review highlights that regular resistance training can help older women maintain independence and improve their overall quality of life. Additionally, the narrative review suggests that resistance training may also have beneficial effects on other health outcomes, such as cardiovascular health, function, and musculoskeletal health. Overall, the narrative review provides evidence to support the inclusion of resistance training in the exercise regimen of older women to promote healthy aging. This narrative review aims to provide information on the health benefits of resistance training on middle-aged and older women, and proposes a series of recommendations to promote its safe and effective practice, to help them enjoy healthy aging.